Doubt in AEHASH

In this problem why they have taken max(V1, V2) = V - A ? I tried understanding but in vain. Can someone explain ?

I think its just a simple re-arrangement.

I mean, V= result (variable returned by function)


result = result + max(hash(S1), hash(S2))

But before this, result =A (we defined it such)

==> Result = A+max(v1,v2)


Hence, max(v1,v2)=V-A.

They just shuffled the terms here and there. That editorial was kinda hard to understand…idk if its because of my sleepiness atm or what.

1 Like